2013
DOI: 10.1186/2193-9039-2-4
|View full text |Cite
|
Sign up to set email alerts
|

On the differential impact of the recent economic downturn on work safety by nativity: the Spanish experience

Abstract: This paper explores differences in work injury and fatality rates between immigrants and natives and how they may have been impacted by the recent economic downturn. Our focus is on Spain over the 2001-2010 decade -a period of time during which Spain received one of the largest immigrant inflows of any developed economy and subsequently experienced a recession that has raised national unemployment rates above 20 percent. We find that immigrants worked in riskier jobs than natives during this high immigration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…But Nielsen et al (2015) show that changes in reporting behaviour do not seem to play a significant role in the relation between the business cycle and workplace injuries in a Danish context. Various authors have observed the pro-cyclical behaviour of occupational accidents in Spain (e.g., Arango and Valdivia, 2000;Castejón, 2000;Arocena and Núñez, 2005;Martín, 2006;Crespán, 2007 Amuedo-Dorantes andBorra, 2013;De la Fuente et al, 2014). Martín (2006) tries to verify whether the pro-cyclical behaviour of occupational accidents in Spain can be considered a real phenomenon that reflects changes in the working conditions along the economic cycle, or is instead a purely statistical effect.…”
Section: Introductionmentioning
confidence: 99%
“…But Nielsen et al (2015) show that changes in reporting behaviour do not seem to play a significant role in the relation between the business cycle and workplace injuries in a Danish context. Various authors have observed the pro-cyclical behaviour of occupational accidents in Spain (e.g., Arango and Valdivia, 2000;Castejón, 2000;Arocena and Núñez, 2005;Martín, 2006;Crespán, 2007 Amuedo-Dorantes andBorra, 2013;De la Fuente et al, 2014). Martín (2006) tries to verify whether the pro-cyclical behaviour of occupational accidents in Spain can be considered a real phenomenon that reflects changes in the working conditions along the economic cycle, or is instead a purely statistical effect.…”
Section: Introductionmentioning
confidence: 99%
“…Several HIC-based studies (e.g. from Canada, Spain, Germany and the United States) indicate that immigrants are over-represented in physically demanding high-risk jobs including manufacturing, construction and farming (2,3) and have higher rates of occupational injury than native-born workers (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Data gathered from the CSWL have been widely used by academics to investigate a number of issues connected with the Spanish economy and relevant socioeconomic conditions. These include immigrants and immigration policy (see [32][33][34][35][36][37][38]), the Labor market (see [39][40][41][42][43][44][45][46][47][48][49][50][51]), the equity, sustainability, transparency and other aspects of the Public Pension System (see [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]), the impact of the economic crisis (see [67][68][69][70]), the usefulness of the MCVL (see [71][72][73][74][75]), the unemployment ( [76][77][78]…”
Section: Applying the Model To The Continuous Sample Of Working Livesmentioning
confidence: 99%